Exposure to the Epstein–Barr Viral Antigen Latent Membrane Protein 1 Induces Myelin-Reactive Antibodies In Vivo - Lomakin, Yakov; Arapidi, Georgii Pavlovich; Chernov, Alexander; Ziganshin, Rustam; Tcyganov, Evgenii; Lyadova, Irina; Butenko, Ivan Olegovich; Osetrova, Maria; Ponomarenko, Natalia; Telegin, Georgy; Govorun, Vadim Markovich; Gabibov, Alexander; et al. (Frontiers in Immunology, 2017)
Multiple sclerosis (MS) is an autoimmune chronic inflammatory disease of the central nervous system (CNS). Cross-reactivity of neuronal proteins with exogenous antigens is considered one of the possible mechanisms of MS triggering. Previously, we showed that monoclonal myelin basic protein (MBP)-specific antibodies from MS patients cross-react with Epstein-Barr virus (EBV) protein LMP1. In this study, we report that exposure of mice to LMP1 results in induction of myelin-reactive autoantibodies in vivo. We posit that chronic exposure or multiple acute exposures to viral antigen may redirect B cells from production of anti-viral antibodies to antibodies, specific to myelin antigen. However, even in inbred animals, which are almost identical in terms of their genomes, such an effect is only observed in 20-50% of animals, indicating that this change occurs by chance, rather than systematically. Cross-immunoprecipitation analysis showed that only part of anti-MBP antibodies from LMP1-immunized mice might simultaneously bind LMP1. In contrast, the majority of anti-LMP1 antibodies from MBP-immunized mice bind MBP. De novo sequencing of anti-LMP1 and anti-MBP antibodies by mass-spectrometry demonstrated enhanced clonal diversity in LMP1-immunized mice in comparison with MBP-immunized mice. Our findings help to elucidate the still enigmatic link between EBV infection and MS development, suggesting that myelin-reactive antibodies raised as a response toward EBV protein LMP1 are not truly cross-reactive but are primarily caused by epitope spreading.